Fenomena Fear of Missing Out (FOMO) pada Generasi Z dalam Mengikuti Trend Tiktok - Fahsya, Nur Kholizha Putri Andini; Junaidi, Ahmad (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Fear of Missing Out (FOMO) is a psychological phenomenon characterized by the fear of missing out on information, experiences, activities, or the latest trends. This phenomenon can trigger feelings of anxiety, envy, worry, and restlessness. This study examines the FOMO phenomenon experienced by Generation Z in following trends on the TikTok platform as a way to fulfill their social needs. The research employs a qualitative approach with a descriptive method, drawing on several theories, including the media exposure theory, communication psychology theory, self-determination theory, and new media theory. Data was collected through in-depth interviews with Generation Z individuals who actively use TikTok and have experienced FOMO. The findings indicate that TikTok’s interactive features and continuous exposure to trending content contribute to FOMO among Generation Z. To satisfy their social needs, Generation Z tends to follow the latest trends to gain social recognition or acceptance within a particular group, a process accelerated by the viral nature of new media content. Consequently, this phenomenon leads to social anxiety, compulsive behavior in continuously checking trending content, and dependence on the TikTok platform. Fear of Missing Out (FOMO) merupakan fenomena psikologis yang ditandai dengan ketakutan akan ketinggalan informasi, pengalaman, aktivitas, atau tren terkini. Fenomena ini dapat memicu perasaan cemas, iri, khawatir, dan gelisah.Penelitian ini mengkaji fenomena FOMO yang dialami Generasi Z dalam mengikuti tren di platform TikTok sebagai upaya memenuhi kebutuhan sosial. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif serta didasarkan pada beberapa teori, yaitu teori terpaan media, teori psikologi komunikasi, teori self-determination, dan teori media baru. Data diperoleh melalui wawancara mendalam dengan Generasi Z yang aktif menggunakan TikTok dan memiliki pengalaman FOMO. Hasil penelitian menunjukkan bahwa fitur-fitur interaktif serta terpaan konten secara terus-menerus di platform TikTok memicu FOMO pada Generasi Z. Untuk memenuhi kebutuhan sosialnya, Generasi Z cenderung mengikuti tren terbaru guna memperoleh pengakuan sosial atau diterima dalam kelompok tertentu. Hal ini dipercepat oleh persebaran konten viral di media baru. Akibatnya, fenomena ini dapat memicu kecemasan sosial, perilaku kompulsif untuk terus melihat konten trending, serta ketergantungan pada platform TikTok.